Setup of a cryobank for ovarian tissue in a university-based setting - Baston-Büst, Dunja M.; Scheliga, Iwona; Bielfeld, Alexandra P. (Frontiers in Endocrinology, 2023)
Establishing and maintaining a newly set-up cryobank for ovarian tissue in a university setting requires at least 1 year’s notice to start financial, spatial, lab equipment, and employee acquisition planning. Right before and after the start of the cryobank, the newly founded team should introduce itself to the hospitals and local and national health systems via mail, print flyers, and symposia in order to share the possibilities and the knowledge. Potential referrers should be provided with standard operating procedures and advice on getting used to the new system. Especially in the first year after the establishment, all procedures should be internally audited in order to avoid possible difficulties.